Certain heterocyclic compounds containing pyridine and pyrimidine rings : Synthesis, anticaneer and molecular modeling - Ehab Mohammed Abdel Monaem Gedawy; Afaf Kamal Eldin Elansary; Ashraf Ahmed Moneer; Hanan Hassan Kadry (Cairo : Ehab Mohammed Abdelmonaem Gedawy, 2010)
The thesis comprises four chapters. The first one is an introduction which consists of a brief survey on the different methods for the synthesis of pyridothienopyrimidines, thienodipyridines, pyrido [2,3-d] pyrimidines and I,8-naphthyridines and their biological activities. The second chapter involves the objectives of the work and schemes which had been followed to obtain the new target compounds
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Organic Chemistry
Issued also as CD
Keywords: I,8-naphthyridines; Pyridothienopyrimidines; Thienodipyridines